Partnership‐Driven Resources to Improve and Enhance Research (PRIMER): A Survey of Community‐Engaged Researchers and Creation of an Online Toolkit - Dolor, Rowena J. (Blackwell Publishing Inc, 2011)
Objective: This project aimed to develop an open‐access website providing adaptable resources to facilitate best practices for multisite research from initiation to closeout. Methods: A web‐based assessment was sent to the leadership of the Clinical and Translational Science Award (CTSA) Community Engagement Key Functions Committee (n= 38) and the CTSA‐affiliated Primary Care Practice‐based Research Networks (PBRN, n= 55). Respondents rated the benefits and barriers of multisite research, the utility of available resources, and indicated their level of interest in unavailable resources. Then, existing research resources were evaluated for relevance to multisite research, adaptability to other projects, and source credibility. Results: Fifty‐five (59%) of invited participants completed the survey. Top perceived benefits of multisite research were the ability to conduct community‐relevant research through academic–community partnerships (34%) and accelerating translation of research into practice (31%). Top perceived barriers were lack of research infrastructure to support PBRNs and community partners (31%) and inadequate funding to support multisite collaborations (26%). Over 200 resources were evaluated, of which 120 unique resources were included in the website. Conclusion: The PRIMER Research Toolkit (http://www.researchtoolkit.org) provides an array of peer‐reviewed resources to facilitate translational research for the conduct of multisite studies within PBRNs and community‐based organizations. Clin Trans Sci 2011; Volume 4: 259–265